Equilibrium Real Exchange Rates and Capital Flows in Tunisia - Zouhaier, Hadhek; Hniya, Sakli; Lafi, Mosbah (International Journal of Economics and Financial Issues, 2019)
The objective of this paper is to study the impact of the variability (volatility and misalignment) of the real exchange rate (RER) on trade flows over the period 1980-2014.In order to estimate the RER misalignment, we use the methodology of Edwards (1994) which defines the equilibrium RER as a pathway of fundamental variables to ensure internal and external macroeconomic balance. The relation between equilibrium RER and its determiners is obtained by applyingan Error-Correction Model (ECM).Results show that the volatility of the exchange rate causes a decline in exports and imports. The impact of the misalignment is significant only on imports. Keywords: Equilibrium real exchange rate, Misalignment, Cointegration, Export, Import, VECM. JEL Classifications: F14, F62 DOI: https://doi.org/10.32479/ijefi.8795